Attitudes Toward the Use of Code Switching Among Technical Lecturers in UniKL MSI - Zuraidah, Md Noor (2009)
This descriptive study investigates the acceptance and perceptions of UniKL MSI Technical lecturers on the use of code switching in the classroom. Data was gathered by distributing 35 questionnaire using convenient sampling among Technical lecturers. The questionnaires were divided into three parts using Likert Scale. The first part was to access the frequency of using code switching in the classroom, the second part was the attitude towards the use of code switching among Technical lecturers, and the final part was the implications of using code switching in teaching Technical subjects. Apart from the questionnaire, interview sessions with 4 selected respondents were conducted to further substantiate the findings in the questionnaire. The findings suggest that The Technical lecturers consider code switching as an acceptable linguistic behaviour in the classroom. Besides facilitating learning, code switch is also used for giving instruction, to gain feedback, to establish relationship as well as classroom management. Nevertheless, they feel that code switching should be the last resort when teaching and only use it when the situation demands. Code switching is considered as a teaching tool to help the low proficient students to understand the subject matter. At the same time, code switching is seen as hindrance in English language acquisition both to the Technical lecturers as well as the students. All ia all, code switching is acknowledged and acceptable in the context of teaching Technical subjects in UniKL MSI.